Magnitude scales for very local earthquakes. Application for Deception Island Volcano (Antarctica) - Havskov, Jens; Peña, José A; Ibáñez, Jesús M; Ottemöller, Lars; Martı́nez-Arévalo, Carmen (Putting Volcano Seismology in a Physical Context. In memory of Bruno Martinelli, 2003)
Different magnitude scales are calculated for a set of volcano-tectonic earthquakes recorded in Deception Island Volcano (Antarctica). The data set includes earthquakes recorded during an intense seismic series that occurred in January–February 1999, with hypocentral distances that range between 0.5 and 15 km. This data set is enlarged to include some regional earthquakes with hypocentral distances up to 200 km. The local magnitude scale, ML, fixed at a hypocentral distance of 17 km, is used as the reference for the other magnitude scales studied in the present work. ML is determined on a standard Wood–Anderson simulated trace assuming a gain of 2080. Maximum peak-to-peak amplitudes are measured on the vertical components of a short-period sensor. The Mw scale is calculated, in the vertical component, both for P and S waves. The attenuation correction of the ground motion displacement spectra is introduced using data from coda waves studied in the area. The comparison between ML values and Mw estimations indicates severe discrepancies between both values. A magnitude–duration scale is calibrated from the comparison between coda durations of the recorded events and their assigned local magnitude scales. In order to investigate the causes of the discrepancy between the ML and Mw values we analyze two possible error sources: a wrong coda Q value, or the effects of the near-surface attenuation that initially are not taken into account in the correction of the ground displacement spectra. The analysis reveals that the main cause of this discrepancy is the effect of the near-surface attenuation. The near-surface attenuation is also the cause of the determination of an anomalous spectral decay slope, after the corner frequency, and the determination of this corner frequency value. This near-surface attenuation, represented by κ, is estimated over the data set, obtaining an average value of 0.025. With this κ value, the Mw scale is recalculated using an automatic algorithm. The new Mw values are more consistent with the ML values, obtaining a relationship of Mw=0.78ML−0.02.
Keywords: Antarktis; Deceptionøya; geologi; vulkaner

Moment Magnitude Determination for Local and Regional Earthquakes Based on Source Spectra - Ottemöller, Lars; Havskov, Jens (Bulletin of the Seismological Society of America, 2003)
We investigated the use of an automated routine to determine moment magnitudes from the displacement spectra of local and regional earthquakes. Two algorithms, a genetic algorithm and a converging grid search, were developed and tested with earthquake data from Mexico, Norway, and Deception Island (Antarctica). It was found that compared with manual analysis, the algorithms give reliable automatic moment magnitude (Mw) estimates in the range -1 < M < 8. The converging grid search appeared to be more cost-effective than the genetic algorithm. Mw at local and regional distances seems superior to amplitude-based magnitudes that saturate for large earthquakes. The application of the automated algorithm in near real time may help to obtain a nonsaturated magnitude estimate in the case of a large earthquake immediately after the earthquake has occurred. Also, the method can be useful for processing large amounts of data.
Keywords: Antarktis; Deceptionøya; Sør-Shetlandsøyene; seismologi